If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(2y + 3y) = 0 Combine like terms: 2y + 3y = 5y 6(5y) = 0 Remove parenthesis around (5y) 6 * 5y = 0 Multiply 6 * 5 30y = 0 Solving 30y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '30'. y = 0.0 Simplifying y = 0.0
| 2d+14=5d+23 | | 1.1=(1-x) | | 3(x-2)+4.5+1.5(x+1)=-14 | | a+3b+3c=a | | 2(2-3I)=3-(2-7I) | | -I+15+3I+15=-4 | | -x+5=14 | | 720-220x=0 | | 2x^2+14x-35=0 | | (5y-2)+(7-3y)=5 | | f(x)=-4x(x^2-25)(x-5) | | (5y-2)+(7-3y)=6 | | -3(2x+4)=6(4x-2) | | 10p-50=-5p+100 | | 32x+19=211 | | 10g+5(g-12)=0 | | .422h=40 | | y=5.9x+b | | 50+1.75x=39.00+2.50x | | .42(h)=40 | | 0=3+14t-5t^2 | | x^3+2x^1-5x-6=0 | | m+7+-6= | | 0=3?(x)-4/?(x)-4 | | 4(2x-7)=108 | | 8-3(t-4)=2t | | 3(3v+5)=78 | | 3x-7=138+3x | | -8=2(w+4)+20 | | 3(v+6)=42 | | 12n+2=-8 | | -9x+15(37-12)=67 |